2015
DOI: 10.1016/j.pscychresns.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Increased hippocampal blood volume and normal blood flow in schizophrenia

Abstract: Neuroimaging studies have provided compelling evidence for abnormal hippocampal activity in schizophrenia. Most studies made inferences about baseline hippocampal activity using a single hemodynamic parameter (e.g., blood volume or blood flow). Here we studied several hemodynamic measures in the same cohort to test the hypothesis of increased hippocampal activity in schizophrenia. We used dynamic susceptibility contrast- (DSC-) magnetic resonance imaging to assess blood volume, blood flow, and mean transit tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 76 publications
(97 reference statements)
2
32
1
1
Order By: Relevance
“…To our knowledge, this is the first application of the ASL method to investigate differences in resting perfusion in a schizotypy group. Given that the study groups only differed on the presence of schizotypal traits, and that hippocampal hyperperfusion has been reported in patients with psychosis (Friston et al, 1992; Liddle et al, 1992; Malaspina et al, 2004; Pinkham et al, 2011; Schobel et al, 2013, 2009; Talati et al, 2014, 2015; although see Andreasen et al, 1997; Catafau et al, 1994; Early et al, 1987; Parellada et al, 1994), and in people at CHR of sychosis (Allen et al, 2017, 2016; Schobel et al, 2013), our study findings suggest that increased hippocampal activity (reflected in an elevation of regional perfusion) is also involved in the expression of subclinical psychotic‐like experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first application of the ASL method to investigate differences in resting perfusion in a schizotypy group. Given that the study groups only differed on the presence of schizotypal traits, and that hippocampal hyperperfusion has been reported in patients with psychosis (Friston et al, 1992; Liddle et al, 1992; Malaspina et al, 2004; Pinkham et al, 2011; Schobel et al, 2013, 2009; Talati et al, 2014, 2015; although see Andreasen et al, 1997; Catafau et al, 1994; Early et al, 1987; Parellada et al, 1994), and in people at CHR of sychosis (Allen et al, 2017, 2016; Schobel et al, 2013), our study findings suggest that increased hippocampal activity (reflected in an elevation of regional perfusion) is also involved in the expression of subclinical psychotic‐like experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of resting perfusion in patients with schizophrenia spectrum disorders relative to healthy controls, thus, focused predominantly on the hippocampal region. Overall, these studies reported seemingly mixed results, including increases (Friston, Liddle, Frith, Hirsch, & Frackowiak, 1992; Liddle et al, 1992; Malaspina et al, 2004; Pinkham et al, 2011; Schobel et al, 2013, 2009; Talati et al, 2014; Talati, Rane, Skinner, Gore, & Heckers, 2015), decreases (Kindler et al, 2015; Nordahl et al, 1996; Scheef et al, 2010; Tamminga et al, 1992), or no differences (Horn et al, 2009; Ota et al, 2014; Vita et al, 1995). Beyond the hippocampus, other brain regions of significantly elevated resting perfusion in schizophrenia patients compared with healthy controls have involved the basal ganglia and middle temporal lobes (Pinkham et al, 2011), cerebellum, brainstem, and thalamus (Scheef et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The same time point was chosen for the schizophrenia patients, since recent evidence suggests no differences in hippocampal blood flow or mean transit time in schizophrenia (Talati et al, 2015). To account for individual differences in arterial arrival time in the hippocampus, a secondary analysis was performed that determined the best inversion time for each subject based on the maximum difference signal between the control and null images.…”
Section: Methodsmentioning
confidence: 99%
“…While neurovascular coupling has allowed for the examination of hippocampal cerebral blood flow (CBF) and blood volume (CBV) as proxies for neural activity, CBF may not be a good surrogate in medicated patients because antipsychotic medications can ‘normalize’ blood flow in the hippocampus (Lahti et al, 2006; Lahti et al, 2009; Medoff et al, 2001). Some initial studies suggest that CBV is not affected by antipsychotic medications (Schobel et al, 2009; Talati et al, 2014), which may explain uncoupling between these two hemodynamic parameters in schizophrenia (Talati et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation